PENGARUH BUDAYA ORGANISASI DAN DUKUNGAN MANAJEMEN PUNCAK TERHADAP KENERJA PEGAWAI PEMERINTAH PROVINSI SULAWESI TENGGARA - Muhammad Basri; Rosfiah Arsal; Rahman (Journal Publicuho, 2023)
This study aims to examine the influence of organizational culture and top management support on the performance of Southeast Sulawesi Provincial Government employees. This type of data is quantitative data sourced from 673 employee respondents using a questionnaire instrument in the form of a google form as a data collection technique. The sampling technique is random sampling. The data was processed using the SPSS Version 25 statistical package program and analyzed by multiple regression. The results showed that organizational culture and top management support had a significant effect on performance. The more consistent the implementation of organizational culture and the stronger the support of top management, it will have a positive impact on improving employee performance to encourage innovation, so that organizational culture and top management support are strategic assets to improve performance internally